Habitat use, richness, and abundance of native mice in the highlands of the Talamanca mountain range, Costa Rica - Ramírez-Fernández, José D.; Barrantes, Gilbert; Sánchez-Quirós, Catalina; Rodríguez-Herrera, Bernal (THERYA, 2023)
The Costa Rican highlands are considered hotspots of diversity and endemism, but studies on rodents are scarce. We compared the richness and abundance of mice between the montane forest and the paramo at the summit of the Talamanca mountain range. We selected two study sites within the Talamanca mountain range: the Cerro de la Muerte Biological Station and the paramo. The former is a montane forest dominated by oaks, and the latter is dominated by an herbaceous layer, and some scattered bushy patches. We captured mice in two different microhabitats within each montane forest and paramo, so we had four different sampling microhabitats: (1) paramo–bush, (2) paramo–Chusquea, (3) montane forest–bush, and (4) montane forest–Chusquea. Mice were marked to identify recaptures. We captured four mouse species and their abundance varied largely between habitats and among microhabitats (Table 1). The most abundant species, representing 85 % of all mouse captures, was Peromyscus nudipes. Mice were more abundant in the montane forest than in the paramo. Within the montane forest, mice were more abundant in the microhabitat containing bushes. The montane forest has a more complex vegetation structure with more diversity of food resources and shelters than the paramo. As well as at the habitat level, we argue that differences in abundance among microhabitats are directly related with the structure of vegetation. A more complex habitat structure may provide rodents with better conditions.